Penguatan Literasi Digital dan Etika Bermedia Mahasiswa PIAUD Generasi Z sebagai Calon Pendidik Anak Usia Dini melalui Pendidikan Islam : Strengthening Digital Literacy and Media Ethics of Generation Z PIAUD Students as Prospective Early Childhood Educators through Islamic Education - Dian Sukma Lutfiana; Muhammad Nur Ghufron; Novita Pancaningrum (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
The development of digital technology has shaped the characteristics of Generation Z as a generation that grew up with the internet and social media. Students of the Early Childhood Islamic Education Study Program (PIAUD), who fall into the Generation Z category, have a high affinity for digital technology, but this affinity is not always accompanied by adequate digital literacy and media ethics skills. As prospective early childhood educators, PIAUD students are required not only to be technologically proficient but also to have a moral responsibility in the use of digital media. This research aims to analyze the strengthening of digital literacy and media ethics among Generation Z PIAUD students thru Islamic education. The study employs a qualitative approach with a literature review method, analyzing various relevant literature related to digital literacy, media ethics, Generation Z characteristics, and Islamic education values. The findings indicate that the integration of Islamic education values, such as responsibility, honesty, tabayyun (clarification), and self-control, plays a significant role in shaping the digital character of PIAUD students. This strengthening serves as an important foundation in preparing students to become professional, ethical, and adaptive early childhood educators in response to technological developments. Thus, Islamic education has a strategic contribution in building digital literacy competencies that are oriented toward character formation and social responsibility in the digital era.   ABSTRAK  Perkembangan teknologi digital telah membentuk karakteristik Generasi Z sebagai generasi yang tumbuh bersama internet dan media sosial. Mahasiswa Program Studi Pendidikan Islam Anak Usia Dini (PIAUD) yang termasuk dalam kategori Generasi Z memiliki kedekatan yang tinggi dengan teknologi digital, namun kedekatan tersebut tidak selalu diiringi dengan kemampuan literasi digital dan etika bermedia yang memadai. Sebagai calon pendidik anak usia dini, mahasiswa PIAUD dituntut tidak hanya cakap secara teknologi, tetapi juga memiliki tanggung jawab moral dalam penggunaan media digital. Penelitian ini bertujuan untuk menganalisis penguatan literasi digital dan etika bermedia mahasiswa PIAUD Generasi Z melalui pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka yang menganalisis berbagai literatur relevan terkait literasi digital, etika bermedia, karakteristik Generasi Z, serta nilai-nilai pendidikan Islam. Hasil kajian menunjukkan bahwa integrasi nilai-nilai pendidikan Islam, seperti tanggung jawab, kejujuran, tabayyun, dan pengendalian diri, berperan signifikan dalam membentuk karakter digital mahasiswa PIAUD. Penguatan tersebut menjadi fondasi penting dalam mempersiapkan mahasiswa sebagai calon pendidik anak usia dini yang profesional, beretika, dan adaptif terhadap perkembangan teknologi. Dengan demikian, pendidikan Islam memiliki kontribusi strategis dalam membangun kompetensi literasi digital yang berorientasi pada pembentukan karakter dan tanggung jawab sosial di era digital.